100k views
2 votes
If f(x) = -2x + 7 and g(x) = x2 – 2, then f(g(3)) is
equal to

User Skub
by
5.9k points

1 Answer

2 votes

Answer:

f(g(3)) = -7

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Algebra I

  • Functions
  • Function Notation

Explanation:

Step 1: Define

Identify

f(x) = -2x + 7

g(x) = x² - 2

Step 2: Find f(g(3))

  1. Substitute in x [Function g(x)]: g(3) = 3² - 2
  2. Evaluate exponents: g(3) = 9 - 2
  3. Subtract: g(3) = 7
  4. Substitute in g(3) [Function f(x)]: f(g(3)) = -2(7) + 7
  5. Multiply: f(g(3)) = -14 + 7
  6. Add: f(g(3)) = -7
User Viarnes
by
6.1k points